Intra-tumoral drug concentration mapping within solid tumor micro-milieu using in-vitro model and doxorubicin as a model drug - Ahmed M. Al-Abd; Alaa Khedr; Salah G. Atteiah; Fahad A. Al-Abbasi (Elsevier, 2020)
In contrast to plasma pharmacokinetics, intratumoral pharmacokinetics of doxorubicin (DOX) determines its spatial anti-tumoral activity. Three-dimensional multicellular layers (MCL) model for solid tumors present optimum experimental platform for studying the intratumoral pharmacokinetics of DOX. This might imply new insights for understanding intratumoral pharmacokinetic parameters with realistic clinical implications. Herein, we are presenting simplified method for the spatial in-situ concentration assessment of DOX within the avascular simulating MCL solid tumor model of DLD-1 and HT-29 cell lines. DLD-1 and HT-29 formed viable well-structured MCL model abundant in extracellular matrix component (fibronectin). DOX (100 µM) showed stronger anti-proliferative effect against MCL of DLD-1 compared to HT-29 MCL (38.8% and 27.9%, respectively). The differential potencies of DOX closely correlate to the intratumoral pharmacokinetics within MCL's of both cell lines. DOX penetrated faster and washed out slower through the MCL of DLD-1 compared to HT-29 MCL. Distribution of DOX within MCL of DLD-1 was more homogenous compared to HT-29 MCL. Tissue concentration of DOX within MCL of DLD-1 was significantly higher than HT-29 MCL's after 96 h exposure (0.7 and 0.4 µmole/gm tissue, respectively). Concentration of DOX within MCL of both cell lines exceeded the IC50 under monolayer conditions (2.3 ± 0.6 µM and 0.6 ± 0.1 µM, respectively). In addition, DOX was extensively metabolized to less active metabolites (doxorubicinol and doxorubicinone) through the thickness of both MCL's. In conclusion, Intratumoral pharmacokinetic barriers to DOX might be key determinant in drug resistance on the tissue level, despite cellular and molecular events.